2004
DOI: 10.3354/dao061175
|View full text |Cite
|
Sign up to set email alerts
|

Detection and quantification of Spironucleus barkhanus in experimentally infected Atlantic salmon Salmo salar

Abstract: The course of Spironucleus barkhanus (Diplomonadida: Hexamitidae) infection in Atlantic salmon Salmo salar L. (Salmonidae) has 2 distinct phases, a blood phase and a tissue phase. To detect and quantify an infection, 3 parasitological techniques, namely Wet Mount Examination (WME), Hematocrit Centrifuge Technique (HCT) and the Hemocytometer (HCM) were used. In addition, 1 immunological technique, enzyme-linked immunosorbent assay (ELISA), was developed to detect specific antibodies against S. barkhanus. This t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Three techniques -Wet Mount Examination (WME), Hematocrit Centrifuge Technique (HCT; Woo 1969) and Hemocytometer (HCM; Archer 1965) -were used for the detection and quantitation of parasites in the blood. WME was used for mucus detection; WME and HCM were used for tissues and organs (Guo & Woo 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Three techniques -Wet Mount Examination (WME), Hematocrit Centrifuge Technique (HCT; Woo 1969) and Hemocytometer (HCM; Archer 1965) -were used for the detection and quantitation of parasites in the blood. WME was used for mucus detection; WME and HCM were used for tissues and organs (Guo & Woo 2004).…”
Section: Methodsmentioning
confidence: 99%
“…For example, Watanabe et al (1998) reported successful prevention of vertical transmission of pathogenic viruses by selection of specific pathogen-free spawners, as indicated by results from an antibody-detection ELISA. However, antibody-detection ELISA has not been accepted internationally because the ELISA system for fish antibody detection has problems, such as low reproducibility partly due to high background optical density (OD) caused by non-specific reactions between fish antibodies and antigens (Olesen et al 1991, Höglund & Pilström 1995, Knopf et al 2000, Kibenge et al 2002, Guo & Woo 2004. We have experienced similar problems with ELISA systems used for detection of fish antibodies against pathogenic viruses, infectious hematopoietic necrosis virus, viral hemorrhagic septicemia virus, fish nodavirus, lymphocystis disease virus and koi herpesvirus, etc.…”
Section: Introductionmentioning
confidence: 95%
“…Several studies using ELISA systems for the detection of specific fish antibodies have been reported for aquatic animals (Jorgensen et al 1991;Yoshimizu et al 1992;Dixon et al 1994;Pilström 1994, 1995;LaPatra 1996;Nishida et al 1998;Watanabe et al 1998;Swain and Nayak 2003;Okuda et al 2006;Kim et al 2007Kim et al , 2008Kim et al , 2009Takami et al 2010). However, use of an ELISA for fish antibody detection can be problematic because of difficulties such as low reproducibility, which is partly due to high background optical density (OD) caused by nonspecific reactions between fish antibodies and antigens Pilström 1994, 1995;Knopf et al 2000;Kibenge et al 2002;Guo and Woo 2004). It was reported that one of the most important causes of those problems was the nonspecific adsorption of fish antibodies with ELISA blocking reagents, but nonspecific adsorption can be suppressed by the pretreatment of fish sera with a skim milk solution (Kim et al 2007).…”
mentioning
confidence: 99%